2016
DOI: 10.1002/cncr.30364
|View full text |Cite
|
Sign up to set email alerts
|

Time‐dependent risk and predictors of venous thromboembolism in breast cancer patients: A population‐based cohort study

Abstract: This study confirms the long-term risk of VTE in breast cancer patients and identifies a comprehensive set of clinical risk predictors. Temporal associations with patient, tumor, and treatment characteristics provide insight into the time-dependent etiology of VTE. Cancer 2017;123:468-475. © 2016 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
27
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 43 publications
4
27
1
Order By: Relevance
“…Regarding radiotherapy, in multiple analysis, women in this study who underwent such treatment had no risk of developing DVT. In the Swedish population-based study that included 8,338 breast cancer patients, the radiotherapy showed no association with VTE in multivariable analyses (HR=1.07, 95% CI 0.79-1.47) [16] Begtrupo et al in a prospective clinical study evaluated blood sampling in 39 women who underwent adjuvant radiotherapy after breast cancer in the year 2016 at a Danish center and concluded that radiotherapy did not affect hemostasis evaluated by platelet aggregation and thrombin generation; neither as a single dose nor during the entire radiation course [26].…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Regarding radiotherapy, in multiple analysis, women in this study who underwent such treatment had no risk of developing DVT. In the Swedish population-based study that included 8,338 breast cancer patients, the radiotherapy showed no association with VTE in multivariable analyses (HR=1.07, 95% CI 0.79-1.47) [16] Begtrupo et al in a prospective clinical study evaluated blood sampling in 39 women who underwent adjuvant radiotherapy after breast cancer in the year 2016 at a Danish center and concluded that radiotherapy did not affect hemostasis evaluated by platelet aggregation and thrombin generation; neither as a single dose nor during the entire radiation course [26].…”
Section: Resultsmentioning
confidence: 96%
“…[20] Similarly, in our study, age was risk factor in multiple analyses and chemotherapy was the main risk factor for DVT. Although chemotherapy treatment is associated with an increased risk of thrombosis [11,16,20], the pathogenic mechanisms for the thrombogenic effect of chemotherapeutic drugs are poorly understood [21]. Probably, chemotherapeutic agents are associated with thrombogenic mechanisms, such as reduction in fibrinolytic activity, direct endothelial cells lesions and interaction with the Von Willebrand factor [22].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, we agree that hormonal therapy for breast cancer therapy is a risk factor for VTE,6 and that individuals on such therapy are high-risk travelers. Hence, the guideline applies to them as it applies to individuals with any other risk factor for VTE.…”
mentioning
confidence: 84%
“…It is possible that their different mechanisms of action would be complementary, with the aromatase inhibitor decreasing the estrogen level and thus allowing tamoxifen to function more effectively as a competitive inhibitor with estradiol. In order to mitigate thromboembolic event, which is a serious complication of cancer [ 13 ] and which can be exacerbated by the use of tamoxifen [ 14 ], we proposed the prophylactic use of a low molecular weight heparin, enoxaparin, administered on a daily basis, throughout ovarian stimulation.…”
Section: Introductionmentioning
confidence: 99%